Resistance Status of Dengue Virus Serotype in Aedes Aegypti on The Exposure of Insecticide Temefos and Cypermethrin - Arimaswati, Arimaswati; Alifariki, La Ode; Siagian, Heriviyatno Julika; Tukatman, Tukatman; Rangki, La (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
The success of vector control is influenced by the resistance of Ae. aegypti against insecticides. The continued use of insecticides will leave a resistant population. The study aims to determine the resistance status of dengue virus serotype in Aedes Aegypti on the exposure of Insecticide Temefos and cypermethrin. Mosquitoes are taken directly from the tub and the home environment using the GAMA DOTIK. To determine the status of resistance to organophosphate insecticides in larvae and synthetic pyrethroids in adult mosquitoes, a biological test was carried out using the WHO 1992 method at a diagnostic dose (temefos 0.02 ppm and 0.05% cypermethrin), while the serotype of the dengue virus was determined by the Reverse Transcriptase method. -Polymerase Chain Reaction (RT-PCR) using Lanciotti-specific primers. Endemic areas (Gadingan, Wonosidi Lor and Dipan) are all still susceptible to temefos with 100% larval mortality. Sporadic areas such as Driyan were in a vulnerable status with Mortality Rate (AK) = 100%, Durungan and Kriyanan were in a tolerant status (AK = 88% and 97%). Potential areas such as Kauman and Janten were vulnerable (AK = 100% and 98%), Panjatan was intolerant status (AK = 84%). Endemic, sporadic and potential areas were all resistant with AK = less than 80% to the insecticide cypermethrin. Dengue virus serotypes in endemic areas are dengue 2 and dengue 3. In potential areas, dengue serotype 3 is found, while in sporadic areas there are no virus serotypes. Conclusion: The resistance status of Aedes aegypti in endemic, sporadic and potential areas to organophosphate insecticides (temefos) is in the susceptible to the tolerant range, while all areas status to synthetic pyrethroids (cypermethrin) are resistant. Abstrak: Keberhasilan pengendalian vektor dipengaruhi oleh hambatan Ae. aegypti melawan insektisida. Penggunaan insektisida secara terus menerus akan meninggalkan populasi yang resisten. Penelitian ini bertujuan untuk mengetahui status resistensi serotipe virus dengue Aedes Aegypti terhadap paparan Insektisida Temefos dan cypermethrin. Nyamuk diambil langsung dari bak mandi dan lingkungan rumah menggunakan GAMA DOTIK. Untuk mengetahui status resistensi insektisida organofosfat pada larva dan piretroid sintetik pada nyamuk dewasa, dilakukan uji biologis dengan metode WHO 1992 dengan dosis diagnostik (temefos 0,02 ppm dan 0,05% cypermethrin), sedangkan serotipe virus dengue ditentukan dengan metode Reverse Transcriptase. -Polymerase Chain Reaction (RT-PCR) menggunakan primer khusus Lanciotti. Daerah endemik (Gadingan, Wonosidi Lor dan Dipan) semuanya masih rentan terhadap temefos dengan kematian larva 100%. Daerah sporadis seperti Driyan berada dalam status rawan dengan Angka Kematian (AK) = 100%, Durungan dan Kriyanan dalam status toleran (AK = 88% dan 97%). Wilayah potensial seperti Kauman dan Janten termasuk kategori rawan (AK = 100% dan 98%), Panjatan dalam status toleran (AK = 84%). Daerah endemik, sporadis dan potensial semuanya resisten dengan AK = kurang dari 80% terhadap insektisida cypermethrin. Serotipe virus Dengue di daerah endemis adalah Dengue 2 dan Dengue 3. Di daerah potensial ditemukan Dengue Serotipe 3, sedangkan di daerah sporadis tidak terdapat serotipe virus. Status resistensi nyamuk Aedes aegypti di daerah endemik, sporadis dan potensial terhadap insektisida organofosfat (temefos) berada pada rentang toleran, sedangkan semua status daerah terhadap piretroid sintetis (cypermethrin) resisten.